Extension and Comparision of Free Length Theory and Collision Factor Theory in the Binary Liquid Mixture - Saxena, M.C.; Dubey, Poonam; Tripathi, Ashutosh; Kaur, Amarjeet (Asian Journal of Chemistry, 2011)
In the present investigation, a comparison between the various theories of intermolecular free length, with their merits and demerits have been studied. Jacobson theory (FLT) and collision factor theory (CFT) have been extended to six binary liquid mixture of hexane-benzene, hexanetoluene, hexane-ethyl benzene, heptane-benzene, heptane-toluene, heptane-ethyl benzene at 313.15 K. The interaction between the components of binary mixture have also been studied on the basis of excess free length.